The Important Role of Craftsmanship in The Lifestyle of the Population - Kovulov Jurabek (Global Scientific Publishing, 2022)
The article describes the historical roots of handicrafts in detail, and the definitions given by scientists of each nation to handicrafts are included. Geographical, economic, climatic and ethnic factors that create the basis for the creation of handicrafts are listed. Crafts are divided into small groups according to internal factors to make learning easier.
Keywords: weaving; pottery; blacksmithing; stonework